Non-Hodgkin's lymphoma of tonsils - (:unkn) unknown (My University, 1996)
It is well known that non-Hodgkin's lymphoma of various histologic types, including Burkitt's lymphoma and chronic lymphocytic leukemia (diffuse well-differentiated lymphocytic lymphoma), frequently appears in the oral cavity's soft tissues, including the soft palate and Waldeyer's ring. An unusual case of non-Hodgkin's lymphoma primarily with tonsillar involvement was evaluated. The clinical course of the disease was presented with the current literature search.
Keywords: Lymphoma; Non-Hodgkin's; Tonsil